Forces and tension in development - Labouesse, Michel (Current topics in developmental biology, 2011)
This book presents some of the most advanced experimental systems in which the role of forces has been dissected. It explores the physical principles accounting for how forces can affect soft matter such as our cells, and presents some of the methods used to measure or assess the role of forces. Presents some of the most advanced experimental systems in which the role of forces has been dissected. It explores the physical principles accounting for how forces can affect soft matter such as our cells, and presents some of the methods used to measure or assess the role of forces. Appeals to both physicists eager to get familiar with biological systems, and to biologists curious about the physical principles behind what they observe.